(untitled) (Research, Society and Development, 2022)
The displacement of auxinic herbicides to the non-target site results in agronomic and environmental damages. The objective of this research was to evaluate the effects of doses of the herbicides dicamba and triclopyr applied in the phenological phases V2, V4 and V8 on the corn crop. The treatments were arranged in split plots in a 3x5 arrangement. The herbicide applications ocorred in three maize phenological phases (V2, V4 and V8) and were tested five doses of each herbicide (0; 4.8; 24; 48; 96 g ae. ha-1). The doses of dicamba applied in the V4 phase of the maize crop caused injuries of up to 16.5% at 7 days after application (DAA), with subsequent recovery at 28 DAA. In the phenological phases V2 and V8, the doses of dicamba did not cause damage and did not affect the corn grain yield. For triclopyr, maize plants were more sensitive when the herbicide was applied at V4, with a linear increase with increasing doses. At 21 DAA, symptoms were 50% phytotoxic, but with partial recovery at 28 DAA. Triclopyr applied in phases V2 and V4 promoted a reduction in corn productivity in relation to the application made in V8. The triclopyr dose of 4.8 g a.e ha-1 promoted hormesis effect in corn, with an increase in grain yield in relation to the other doses applied.